A comparative phytochemical profiling of essential oils isolated from three hemp (Cannabis sativa L.) cultivars grown in central-northern Morocco. (July 2022) - El Bakali, Ismail; Sakar, El Hassan; Boutahar, Aboubakr; Kadiri, Mohamed; Merzouki, Abderrahmane
Abstract: Hemp known botanically as Cannabis sativa L. (CS) is an important industrial crop. A huge literature was devoted to its biology owing to its numerous health-healing properties and biotechnological applications. However, little is known about essential oil (CSEO) chemical composition in the cultivars grown in Morocco. In this research work, we aimed at investigating CSEO chemical composition of three cultivars namely: 'Beldiya', 'Mexicana', and 'Critical Plus'. CSEOs were isolated from dried inflorescences using hydrodistillation and then subjected to chemical analysis using GC-MS. Our results showed that CSEOs yield and chemical composition varied significantly among cultivars. 'Critical Plus' showed the greatest record of CSEO yield (0.688%), while 'Mexicana' had the lowest value (0.330%). However, 'Critical Plus' presented the smallest values for the most of major compounds. Chemical composition showed an important phytochemical richness especially terpenoids. The most abundant compounds found in CSEOs were the following: β-caryophellene (13.39–25.32%), β-myercene (10.03–20.09), α-humulene (4.88–8.73%), caryophellene oxide (1.46–6.07%), decane (1.41–4.46%), and α-pinene (1.91–3.66%). The highest records of these compounds were reported in 'Beldiya' (β-caryophellene, caryophellene oxide, and decane) and 'Mexicana' (β-myercene, α-humulene, and α-pinene). Principal component analysis allowed a good separation of the three investigated cultivars based on their essential oil major compounds. It could be concluded that, the studied cultivars were caryophellene chemotypes, the local cultivar 'Beldiya' along with 'Mexicana' performed better in terms of essential oil yield and major phytochemicals over 'Critical Plus'. Highlights: Three investigated cultivars were separated by PCA and CSEO profiling. 'Critical Plus' showed the greatest CSEO record, while Mexicana had the lowest value. 'Critical Plus' presented the smallest values of most major compounds β-caryophellene had the highest record of compounds reported in 'Beldiya' β-myercene had the highest record of compounds reported in 'Mexicana'